Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1021/acsnano.9b06123
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Viscoelastic Microfluidics for Efficient Focusing and Separation of Nanoscale Species

Abstract: The ability to precisely control particle migration within microfluidic systems is essential for focusing, separating, counting, and detecting a wide range of biological species. To date, viscoelastic microfluidic systems have primarily been applied to the focusing, separation, and isolation of micrometer-sized species, with their use in nanoparticle manipulations being underdeveloped and underexplored, due to issues related to nanoparticle diffusivity and a need for extended channel lengths. To overcome such … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 66 publications
0
59
0
Order By: Relevance
“…to manipulate target particles at high sensitivity [71,[119][120][121][122]. Moreover, oscillatory inertial microfluidics can focus smaller-size particles with a small footprint microchannel [123][124][125][126]. Compared with the inertial microfluidics flowing in a constant direction along a pressure gradient, oscillatory flow can switch the flow direction at the high frequency, resulting in the practical infinite microchannel effects.…”
Section: Discussionmentioning
confidence: 99%
“…to manipulate target particles at high sensitivity [71,[119][120][121][122]. Moreover, oscillatory inertial microfluidics can focus smaller-size particles with a small footprint microchannel [123][124][125][126]. Compared with the inertial microfluidics flowing in a constant direction along a pressure gradient, oscillatory flow can switch the flow direction at the high frequency, resulting in the practical infinite microchannel effects.…”
Section: Discussionmentioning
confidence: 99%
“…The strength and flexibility of microfluidic devices that leverage viscoelastic fluid properties have been demonstrated in recent years for nanoparticle sorting (Kang et al, 2013 ; Lim et al, 2014 ; Liu et al, 2016 ; Zhou et al, 2020 ), and specifically for separating EVs (Liu C. et al, 2017 ; Zhou Y. et al, 2019 ; Asghari et al, 2020 ). Viscoelastic focusing is a phenomenon where the flow of a dilute polymer solution, which carries both elastic and viscid properties, can generate forces including elastic lift that then push particles of a specific size and rigidity to an equilibrium position in the fluid channel (Leshansky et al, 2007 ) ( Figure 3B ).…”
Section: Experimental Approachesmentioning
confidence: 99%
“…A sheathless, oscillatory design was shown to focus 20 and 40 nm particles, though it was not shown that they could be separated. This device could distinctly separate small EVs (mean diameter = 122 nm) from large EVs (1–2 μm milk fat globules) (Asghari et al, 2020 ). The flexibility of viscoelastic focusing can also be seen in diversity of viscoelastic fluid preparations.…”
Section: Experimental Approachesmentioning
confidence: 99%
“…Generation of disturbed flows enhances the exchange of mass, momentum, and heat in microfluidic systems benefiting a variety of applications in physics, chemistry, biology, materials sciences, and bioengineering. This includes studying mechanical and rheological properties of complex fluids and soft materials such as polymers, emulsions, colloids, liquid crystals, and their biological counterparts, [5][6][7][8][9][10] chemical synthesis of hazardous chemical compounds, pharmaceutical agents, and micro/nanomaterials, [11][12][13][14] and mimicking harmonic/disturbed flows occurring in the natural systems, such as the human circulatory system, where they may cause dysfunction or disease. [15][16][17][18][19] Passive and active mechanisms have been used to generate disturbed flow patterns in microfluidic systems.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, active mechanisms take advantage of external stimuli to disturb flow. This includes a variety of mechanical, [30][31][32] pneumatic, [10,[33][34][35] thermal, [36] acoustic, [37,38] electrical, [39,40] and electrowetting [41,42] mechanisms to disturb the laminar flow. Despite these advances, their widespread application has been limited by their dependence on additional supporting equipment, which increases the overall size, cost, and complexity of the system, contradicting the principal promises of microfluidics for delivering small, inexpensive, and simple devices.…”
Section: Introductionmentioning
confidence: 99%